Postmodernistyczne formy aktywności politycznej: przykład wydarzeń na Ukrainie (koniec 2013 i 2014 r.) - Hrujeva, Oleksandra (Historia i Polityka, 2017)
The article analyzes the newest formats of socio-political protests. The postmodern forms of political activity are examined on the example of events in Ukraine since the beginning of the Revolution of Dignity. The creativity of the newest non-violent forms of protests (performances, flash mobs, installations, etc.), which were carried out in the revolutionary period and during the subsequent occupation of the part of the territory of Ukraine was proven. It is substantiated that political action in the postmodern reality is provocative and is based on game, ritual and symbolism. The perception of political events through the prism of spectacularity is emphasized.